Factors Influencing Stunting in Indonesia 2018 With Geographically Weighted Regression Analysis - Rizqi Dwi Yuniarsyih R.A,; Hakim Zoelva Mahesa,; I Putu Gde Inov Bagus Prasetya,; Syella Zignora Limba,; Muhammad Nur Aidi,; Yekti Widodo,; Elisa Diana Julianti,; Fitrah Ernawati,; Aya Yuriestia Arifin, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Stunting is a health issue with long-term effects on human resource quality. This study analyzes factors influencing stunting prevalence in Indonesia using the Geographically Weighted Regression (GWR) approach. Using 2018 provincial-level data, the study examines the impact of social, health, and education factors on stunting rates, categorized by gender. Analysis employs Global Regression to identify key explanatory variables before applying GWR to capture spatial variations. Results reveal significant regional differences, where factors such as Insurance, Participation School, Immunization, Happiness, Water, and Years School exhibit varying influences. The GWR model outperforms global regression, achieving R-squared values of 0.6641 (males) and 0.6589 (females), with AIC values of 506.871 and 499.160, respectively. These findings highlight the importance of localized policies to address stunting effectively.
Keywords: Stunting; Quadran Method; Global Regression; Geographically Weighted Regression